Editorial for the Special Issue on "Graphene-Related Materials: Synthesis and Applications" - Otyepka, Michal; Giannakoudakis, Dimitrios A; Bakandritsos, Aristides (Nanomaterials (Basel, Switzerland), 2022)
Since the groundbreaking discovery of graphene by Geim and Novoselov in 2004, there has been continuous research focused on the utilization of graphene (GR) and graphene-related materials (GRms) in technologically high-impact applications, spanning from electronics, sensing, and spintronics, to catalysis, energy storage, and environmental remediation [...].